PENTINGNYA STUDI KRITIK TEKS DALAM EKSEGESIS PERJANJIAN BARU - Adi Putra (Manna Rafflesia, 2023)
This research is about the study of New Testament text criticism. Through this research, the importance of this study in the exegesis of the New Testament is put forward. Thus making text criticism a step that every interpreter must carry out. The main reasons for text-critical studies to be carried out are the damage to the original manuscripts of the New Testament, and the available copies contain so many variants. By using qualitative research methods or, more precisely, literature review, several research results were found related to this research topic. Text-critical studies help interpreters select texts or variants much closer to the damaged versions of the original NT texts to be used as reference texts in the exegesis studies conducted. The study of text criticism helps every interpreter to carry out a scientific interpretation but does not set aside its authority and authority as the revealed Word of God. Finally, through the study of New Testament text criticism, interpreters are taught to build their texts so that any result of the resulting interpretation is no longer in doubt, both in terms of the textual aspect and the theology produced.